Problems of Electronic Evaluation in Jordanian Universities during the Corona Pandemic from the Teachers’ Point of View - Abu Mazer, Maha; Abood , Harith (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed to reveal the problems of electronic evaluation in Jordanian universities during the Corona pandemic from the point of view of their faculty members. The study also contributes to enriching Arabic research on the subject of the electronic calendar. It is expected that the decision-makers in the Ministry of higher education and Jordanian universities will benefit from the development of evaluation mechanisms in them. Methods: The researchers adopted the descriptive approach. The study sample consisted of 181 faculty members randomly selected from among 2500 faculty members from the University of Jordan and the Arab Open University for the academic year 2020/2021. A questionnaire was constructed and distributed to the study sample electronically. Results: The study revealed that the electronic evaluation problems faced by the teachers during the Corona pandemic were different, and that there were statistically significant differences in technical problems due to the university (Jordan / Arab Open University). It showed that females suffered more than their male colleagues in facing the technical problems, and that the teachers with experience of 10 years or more suffered less than those with less experience. Conclusions: The researchers submitted 19 proposals to address the problems they faced in preparing, evaluating and managing tests during the pandemic